Pengaruh Makroekonomi terhadap Pembiayaan Mudharabah pada Bank Umum Syariah dan Unit Usaha Syariah - Uswatun Hasanah; Ruhadi Ruhadi; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine whether there is a significant effect of macroeconomic variables on the mudharabah financing variable, partially or simultaneously. The dependent variable used in this study is Mudharabah Financing, while the independent variables used in describing macroeconomic changes include the Inflation Rate, Exchange Rate, BI Rate, and the Money Supply. Using secondary data derived from the monthly Sharia Banking Statistics report from OJK for the period January 2016 – November 2020, Economic and Financial Statistics (SEKI-BI) published by BI and the Central Statistics Agency. The population in this study were 14 Sharia Commercial Banks and 20 Sharia Business Units registered with the OJK. This research is a time series. The research method used is descriptive quantitative. The data analysis technique used is multiple linear regression analysis. The results showed that simultaneously the variables of inflation, exchange rate, BI rate and the money supply did not have a significant effect on mudharabah financing and partially inflation had a positive and significant effect on mudharabah financing while the exchange rate, BI rate and money supply had no significant effect to mudharabah financing.